Computational fluid dynamic modelling of a waste-heat boiler associated with flash smelting of base metal sulphides - Bezuidenhout, J.; Yang, Y.; Eksteen, Jacques (Southern African Institute of Mining and Metallurgy, 2008)
The waste-heat boiler is used within the Sulphide flash smelting process as the main dust and energy recovery unit. The large volume of off-gas discharged from the flash smelter is at a very high temperature (1350°C) and contains a significant dust load that subjects the downstream waste-heat boiler to tough and demanding conditions. The boiler cavity is especially prone to dust accretions, fouling, and corrosion caused by accumulation of molten particles and precipitation of sulphuric acid. Computational fluid dynamics (CFD) is applied within a qualitative study to model the flow and heat transfer distribution throughout the waste-heat boiler. The commercial CFD package, Fluent 6.2.16, was applied to a modified waste-heat boiler (23 m × 11 m × 5.4 m) within the Outokumpu flash smelting process. This investigation focuses on the geometric modifications to the typical boiler design, which includes elevation of the ceiling, placement of flow-obstructing baffles and radiation plates parallel within the flow path. Also investigated were various boiler operating conditions such as the circulation of process off-gas, air leakage from the dust discharging hoppers and variation in inlet gas composition. The geometric modifications had the desired effect of increasing the volumetric utilization and therefore enhancing heat transfer between the boiler surface and the gas stream and dust segregation. Introducing circulated off-gas at a rate of 20 m/s and at a 45° angle to the front of the waste boiler further enhanced cooling while reducing the high impact of the furnace-uptake gas-stream on the boiler ceiling. The placement of radiation plates was found to be very effective in enhancing the heat transfer surface and distributing gas flow within the boiler. These results present recommendations towards an improved waste-heat boiler design. © The Southern African Institute of Mining and Metallurgy, 2007.